The Evolution of Dynamic Capability Theory Toward Dynamic Capability Theory 4.0 - Aditya Halim Perdana Kusuma Putra; Syamsuri Rahim; L. Laela; Najla Gadira Amrul; Zanrina Nurul Safhira (Golden Ratio of Mapping Idea and Literature Format, 2026)
Dynamic Capability Theory has undergone substantial conceptual development since its emergence in the 1990s, evolving from a process-oriented explanation of organizational adaptation into a multidimensional framework encompassing managerial, cognitive, social, relational, and systems-level mechanisms. This study examines the evolution of Dynamic Capability Theory and conceptualizes its contemporary development as Dynamic Capability Theory 4.0. Using a conceptual literature review and comparative synthesis of 101 studies on dynamic capabilities, the analysis traces the theoretical development across four evolutionary stages, from organizational routines and path-dependent processes to explicit microfoundations, managerial agency, social interaction, and multilevel systems integration. The findings demonstrate that the evolution of the theory is characterized by a progressive shift from implicit organizational routines toward the integration of sensing, seizing, and reconfiguring mechanisms with managerial cognition, entrepreneurial leadership, organizational design, interpersonal interaction, collective construction, and relational dynamics. Dynamic Capability Theory 4.0 therefore positions dynamic capabilities not merely as organizational routines or isolated managerial actions, but as capabilities emerging from interactions among individuals, managers, organizational structures, relational networks, and environmental conditions. This perspective also reconciles path dependence with managerial agency and emphasizes flexible, decentralized, and adaptive organizational systems. The study contributes to the dynamic capability literature by providing an integrative evolutionary perspective that connects previously fragmented theoretical streams. Nevertheless, the theory remains conceptually evolving, requiring further empirical validation, clearer construct boundaries, and stronger multilevel operationalization across different organizational and environmental contexts.